2022
DOI: 10.7554/elife.79661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine D2/3 and opioid receptor antagonism on the trade-off between model-based and model-free behaviour in healthy volunteers

Abstract: Human behaviour requires flexible arbitration between actions we do out of habit and actions that are directed towards a specific goal. Drugs that target opioid and dopamine receptors are notorious for inducing maladaptive habitual drug consumption; yet, how the opioidergic and dopaminergic neurotransmitter systems contribute to the arbitration between habitual and goal-directed behaviour is poorly understood. By combining pharmacological challenges with a well-established decision-making task and a novel comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 108 publications
0
14
0
Order By: Relevance
“…This partially opposing mechanistic relationship between dopaminergic and cholinergic neurotransmission during the effort discounting task is further reflected in changes in choice stochasticity. Previous studies have linked D2 receptor antagonism with increased choice stochasticity (Eisenegger et al, 2014;Mikus et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This partially opposing mechanistic relationship between dopaminergic and cholinergic neurotransmission during the effort discounting task is further reflected in changes in choice stochasticity. Previous studies have linked D2 receptor antagonism with increased choice stochasticity (Eisenegger et al, 2014;Mikus et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research links tonic dopamine at D2/D3 receptors to efficient encoding of meaningful stimuli and Bayes optimality (Nour et al, 2018), cognitive control (Cools & D’Esposito, 2011), and sustained attention (Saeedi et al, 2016). Under the model-based, model-free control framework (Daw et al, 2005), recent work showed D2/D3 antagonism increased model-based control and decision flexibility (Mikus et al, 2022a) and increased belief flexibility during a trust game (Mikus et al, 2022b). This may be particularly useful in ‘climbing out’ of paranoia, where one is reluctant to take in positive information about others for fear of ‘false reassurance’.…”
Section: Discussionmentioning
confidence: 99%
“…Following from our preregistered behavioural experiment (Barnby et al, 2020a), we further examine the causal influence of D2/D3 dopamine receptor antagonism on computational mechanisms governing intentional attributions within a simple game theoretic context. Using a formal model of intentional attributions and an iterative Dictator game (Barnby et al, 2020a;2022a), we test the impact of haloperidol, a D2/D3 antagonist, and L-DOPA, a presynaptic dopamine potentiator, on paranoid beliefs using past data (Barnby et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations